Indirect Spectrofluorometric Method for the Determination of Cefotaxime Sodium, Ciprofloxacin Hydrochloride and Famotidine in Pharmaceuticals Using Bromate-Bromide and Acriflavine Dye - Saeed et al. (مجلة بغداد للعلوم)
An Indirect simple sensitive and applicable spectrofluorometric method has been developed for the determination of Cefotaxime Sodium (CEF), ciprofloxacin Hydrochloride (CIP) and Famotidine (FAM) using reaction system bromate-bromide and acriflavine (AF) as fluorescent dye. The method is based on the oxidation of drugs with known excess bromate-bromide mixture in acidic medium and subsequent determination of unreacted oxidant by quenching fluorescence of AF. Fluorescence intensity of residual AF was measured at 528 nm after excitation at 402 nm. The fluorescence-concentration plots were rectilinear over the ranges 0.1-3.0, 0.05-2.6 and 0.1-3.8 µg ml-1 with lower detection limits of 0.013, 0.018 and 0.021 µg ml-1 and quantitation limits of 0.044, 0.060 and 0.069 µg ml-1 for CEF, CIP and FAM respectively. The common excipients and additives didn’t interfere in their determination. The developed method was successfully applied for determination of the studied drugs in their dosage forms resulted in a good agreement with standard British pharmacopeia method and standard addition procedure.